Learner Identity, Learner Agency, and the Assessment of Language Proficiency: Some Reflections Prompted by the Common European Framework of Reference for Languages. (13th March 2015) - Little, David; Erickson, Gudrun
ABSTRACT: This article starts from the assumption that education is a process of "people shaping" designed to help learners extend and perhaps in some ways modify their identity while exploiting and developing their agency. This view is harmonious with the approach to language education that the Council of Europe has developed since the 1970s, and especially with its early commitment to learner autonomy and self-assessment. The approach adopted by the Common European Framework of Reference for Languages: Learning, teaching, assessment (CEFR) to the description of language proficiency clearly implicates the user-learner's identity and agency, which are also central to the CEFR's companion piece, the European Language Portfolio (ELP), in which self-assessment plays a key role. The article proposes that taken together, the CEFR and the ELP imply an assessment culture in which learning and assessment are reciprocally integrated. From the perspective thus established, the authors review some current trends in language assessment and their potential impact on learner identity and learner agency, focusing in turn on self-assessment, peer assessment, teacher assessment, and large-scale testing and assessment. The article concludes by arguing that although recent developments in language assessment pay significantly more attention to the learner than was previously the case, a great deal of work remains to be done to further increase the engagement of learner agency in processes of self-assessment and peer assessment and to align them with other forms of assessment.